Lithium-sulfur batteries with improved life performance.

By employing an SSE electrolyte system without nitrile solvents and a high surface area carbon material at the positive electrode, the lithium-sulfur battery achieves improved lifetime performance and high energy density, addressing the polysulfide shuttle and stability issues in existing technologies.

JP7670854B2Active Publication Date: 2025-04-30LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023561380
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-18
Filing Date
2022-12-09
Publication Date
2025-04-30
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

Lithium-sulfur batteries face challenges in achieving long lifetime performance due to issues like polysulfide shuttle, electrolyte side reactions, and lithium metal instability, which reduce their capacity and lifespan.

Method used

The use of a sparingly solvent-solvating (SSE) electrolyte system without nitrile-based solvents, combined with a carbon material of high specific surface area at the positive electrode, allows for the utilization of over 80% of sulfur's theoretical discharge capacity while preventing lithium anode degradation and gas generation.

Benefits of technology

This approach enhances the lithium-sulfur battery's lifetime performance, enabling it to operate effectively with a high energy density of about 400Wh/kg or 600Wh/L or more, while maintaining a porosity of less than 60%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670854000002
    Figure 0007670854000002
  • Figure 0007670854000001
    Figure 0007670854000001
Patent Text Reader

Abstract

A lithium-sulfur battery is disclosed that utilizes more than 80% of the theoretical discharge capacity of sulfur (1,675mAh / g) by using an SSE (sparingly solvating electrolyte) electrolyte system (discharge capacity ~1,600mAh / gs) that does not use nitrile-based solvents and by applying a carbon material with a high specific surface area to the positive electrode, and thus has improved life performance and can operate over a long life span. The lithium-sulfur battery includes an electrolyte including a first solvent including a fluorine-based ether compound, a second solvent including a glyme-based compound, and a lithium salt including lithium bis(pentafluoroethanesulfonyl)imide; and a positive electrode including sulfur and a carbon material as active materials.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0007015 dated January 18, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a lithium-sulfur battery with excellent life performance, and more particularly, to a lithium-sulfur battery with improved life performance that can utilize 80% or more of the theoretical discharge capacity of sulfur (1,675mAh / g) by using an SSE (sparingly solvating electrolyte) electrolyte system (discharge capacity: 1,600mAh / gs) that does not contain nitrile solvents and by applying a carbon material with a high specific surface area to the positive electrode, and thus can operate with a long life. [Background technology]

[0003] As interest in energy storage technology continues to grow, the fields of application are expanding to include mobile phones, tablets, laptops, and camcorders, as well as the energy of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and research and development of electrochemical devices is gradually increasing. Electrochemical devices are the field that is attracting the most attention in this regard, and among them, the development of secondary batteries such as rechargeable lithium-sulfur batteries is attracting attention, and recently, the development of such batteries has led to research and development of new electrodes and battery designs in order to improve capacity density and specific energy.

[0004] Among these electrochemical devices, the Lithium-S battery has a high energy density (theoretical capacity) and is in the limelight as a next-generation secondary battery that can replace lithium-ion batteries. In such lithium-sulfur batteries, a sulfur reduction reaction and a lithium metal oxidation reaction occur during discharge, at which point sulfur changes from a ring-structured S8 to a linear-structured lithium polysulfide (LiPS). The lithium-sulfur battery is characterized by a stepwise discharge voltage until the polysulfide is completely reduced to Li2S.

[0005] However, the biggest obstacle to the commercialization of lithium-sulfur batteries is their lifespan, as the charge / discharge efficiency decreases during the charging and discharging process, shortening the battery's lifespan. There are various reasons why the lifespan of lithium-sulfur batteries deteriorates, including electrolyte side reactions (accumulation of by-products due to electrolyte decomposition), lithium metal instability (dendrites grow on the lithium negative electrode, causing a short circuit), and accumulation of by-products on the positive electrode (emission of lithium polysulfides from the positive electrode).

[0006] That is, in batteries that use sulfur-based compounds as the positive electrode active material and an alkali metal such as lithium as the negative electrode active material, lithium polysulfide emanation and shuttle phenomenon occurs during charging and discharging, and the lithium polysulfide is transferred to the negative electrode, reducing the capacity of the lithium-sulfur battery, which causes a major problem of reduced lifespan and reduced reactivity. That is, polysulfide emanation from the positive electrode has high solubility in organic electrolyte, so unwanted migration (PS shuttling) to the negative electrode through the electrolyte occurs, resulting in a reduction in capacity due to irreversible loss of the positive electrode active material and a reduction in battery life due to the deposition of sulfur particles on the lithium metal surface due to side reactions.

[0007] Meanwhile, the behavior of such lithium-sulfur batteries can vary greatly depending on the electrolyte. When sulfur in the positive electrode is released into the electrolyte in the form of lithium polysulfide (LiPS), the electrolyte is called catholyte, and when sulfur is hardly released in the form of lithium polysulfide, the electrolyte is called SSE (sparingly solvating electrolyte). The existing lithium-sulfur battery that uses the catholyte system is Li2S x Since it relies on a liquid-phase reaction (catholyte type) through the generation of intermediate products (intermediate polysulfides) with different morphologies, it is not possible to fully utilize the high theoretical discharge capacity of sulfur (1,675mAh / g), and there is a problem in that the battery life is rapidly reduced due to battery degradation caused by the emergence of polysulfides.

[0008] Meanwhile, recently, SSE (sparing solvating electrolyte) electrolyte systems that can suppress the generation of polysulfides have been developed, making it possible to utilize more than 80% of the theoretical discharge capacity of sulfur. However, most SSE electrolyte systems rely on nitrile-based solvents, which cause the lithium anode to degrade due to reactions with the lithium anode, and also generate gas inside the lithium-sulfur battery, which are fatal shortcomings in the battery life.

[0009] Therefore, various researches are being conducted in the industry on lithium-sulfur batteries in which sulfur, the positive electrode active material, does not leak into the electrolyte (researches on adding LiPS adsorbent to the positive electrode composite, modifying existing separation membranes made of PE, etc.), and in particular, researches are being conducted on electrolytes in which sulfur can promote solid-to-solid reactions with Li2S, the final discharge product, but no significant results have been achieved yet. Therefore, there is a demand for the development of innovative batteries with high energy density that use an SSE electrolyte system that can utilize more than 80% of the theoretical discharge capacity of sulfur, without deteriorating the lithium negative electrode or generating gas inside the battery (i.e., improving the battery life) (*A high energy density means more than 400Wh / kg or more than 600Wh / L, and to build this, a battery with a capacity of 4.0mAh / cm is required). 2 Therefore, an electrolyte and positive electrode active material system that can operate even with a porosity of 60% or less is required. Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, the object of the present invention is to provide a lithium-sulfur battery with improved life performance that can operate for a long life by utilizing 80% or more of the theoretical discharge capacity of sulfur (1,675mAh / g) by using an SSE (sparingly solvating electrolyte) electrolyte system (discharge capacity: 1,600mAh / gs) free of nitrile solvents and applying a carbon material with a high specific surface area to the positive electrode. [Means for solving the problem]

[0011] To achieve the above object, the present invention provides a lithium-sulfur battery including: an electrolyte including a first solvent including a fluorinated ether compound, a second solvent including a glyme compound, and a lithium salt including lithium bis(pentafluoroethanesulfonyl)imide; and a positive electrode including sulfur and a carbon material as active materials. Effect of the Invention

[0012] The lithium-sulfur battery with improved life performance according to the present invention uses an SSE (sparingly solvating electrolyte) electrolyte system (discharge capacity of up to 1,600mAh / gs) that does not use nitrile solvents, and at the same time, a carbon material with a high specific surface area is applied to the positive electrode, making it possible to utilize more than 80% of the theoretical discharge capacity of sulfur (1,675mAh / g), and thus has the advantage of being able to operate with a long life. In addition, the lithium-sulfur battery with improved life performance according to the present invention has a discharge capacity of 4.0mAh / cm 2 In addition, by providing an electrolyte and positive electrode active material system that can be operated even with a porosity of 60% or less, the battery also has the advantage of maintaining a high energy density of about 400Wh / kg or more or 600Wh / L or more. [Brief description of the drawings]

[0013] [Figure 1] 1 is a graph showing discharge capacity and life characteristics of lithium-sulfur batteries manufactured according to an embodiment and a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below.

[0015] The lithium-sulfur battery according to the present invention includes an electrolyte including a first solvent including a fluorinated ether compound, a second solvent including a glyme compound, and a lithium salt including lithium bis(pentafluoroethanesulfonyl)imide; and a positive electrode including sulfur and a carbon material as active materials.

[0016] Recently, the SSE (sparing solvating electrolyte) electrolyte system, which can suppress the generation of polysulfide, has been developed, making it possible to utilize more than 80% of the theoretical discharge capacity of sulfur. However, due to the characteristics of the SSE electrolyte system, which relies on nitrile-based solvents, there are still problems that the lithium anode degrades due to reaction with the lithium anode, and that gas is generated inside the lithium-sulfur battery, shortening the battery life.

[0017] Therefore, the present applicant has developed a SSE electrolyte system that can utilize sulfur at a rate of 80% or more, preferably 90 to 100%, and more preferably 94 to 100% of the theoretical discharge capacity, while eliminating the nitrile-based electrolyte solvent, which is fatal to the life of a lithium-sulfur battery, and using a stable ether-based electrolyte solvent, thereby achieving a discharge capacity of 4.0 mAh / cm without deteriorating the lithium negative electrode or generating gas inside the battery (i.e., improving the life). 2 As mentioned above, the company has developed a lithium-sulfur battery with a high energy density of more than 400Wh / kg or more than 600Wh / L by providing an electrolyte and positive electrode active material system that can be operated even with a porosity of 60% or less. Meanwhile, the "sulfur utilization rate" is specifically the ratio of the discharge capacity (mAh) per weight (gram) of the sulfur element contained in the positive electrode of the battery to the theoretical capacity per weight of sulfur, 1,675mAh / g (sulfur). For example, when the discharge capacity per weight of the sulfur element present in the positive electrode of a lithium-sulfur battery is 1,600mAh / g (sulfur), the sulfur utilization rate is 95.5% (1,600 / 1,675).

[0018] That is, the applicant has searched for a solution to the problem of the existing technology that could not maximize the battery performance even though it uses the SSE electrolyte system, and has confirmed a synergistic effect between an electrolyte including a first solvent including a fluorine-based ether compound, a second solvent including a glyme-based compound, and a lithium salt including lithium bis(pentafluoroethanesulfonyl)imide, and a positive electrode including sulfur and a carbon material as an active material. Through this, the applicant has invented a lithium-sulfur battery that can utilize 80% or more of the theoretical discharge capacity of sulfur (i.e., the initial discharge capacity of the battery is at least 1,340mAh / g), preferably 90 to 100%, and more preferably 94 to 100%, and has a high energy density of about 400Wh / kg or more or 600Wh / L or more.

[0019] Hereinafter, A) the first solvent containing a fluorine-based ether compound, B) the second solvent containing a glyme-based compound, C) the lithium salt, and D) the positive electrode contained in the lithium-sulfur battery of the present invention will be specifically described.

[0020] A) First Solvent The first solvent is an electrolyte solvent containing a fluorine-based ether compound, and has the effect of dissolving polysulfide and suppressing solvent decomposition, thereby improving the coulombic efficiency (CE) of the battery, and ultimately improving the life of the battery. More specifically, the first solvent containing a fluorine-based ether compound has excellent solvent structural stability and is very stable compared to general organic solvents containing alkanes due to fluorine substitution. Therefore, when this is used as an electrolyte for a lithium-sulfur battery, the stability of the electrolyte can be greatly improved, and the life performance of the lithium-sulfur battery can be improved.

[0021] The fluorine-based ether compound may include, but is not limited to, one or more selected from the group consisting of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), bis(fluoromethyl)ether, 2-fluoroethyl methyl ether, bis(2,2,2-trifluoroethyl)ether, propyl 1,1,2,2-tetrafluoroethyl ether, isopropyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl isobutyl ether, 1,1,2,3,3,3-hexafluoropropyl ethyl ether, 1H,1H,2'H,3H-decafluorodipropyl ether and 1H,1H,2'H-perfluorodipropyl ether. Among these, it is preferable to include 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether as the first solvent.

[0022] B) Second Solvent The second solvent is an electrolyte solvent that contains a glyme-based compound (but does not contain fluorine) and not only dissolves lithium salt to give the electrolyte lithium ion conductivity, but also releases sulfur, a positive electrode active material, to facilitate the smooth electrochemical reaction with lithium.

[0023] The glyme-based compound may include, but is not limited to, one or more selected from the group consisting of dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether. Among these, it is preferable to include dimethoxyethane as the second solvent.

[0024] C) Lithium salts The lithium salt essentially contains lithium bis(pentafluoroethanesulfonyl)imide (LiBETI) as an electrolyte salt used to increase ionic conductivity.

[0025] The lithium salt may be LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (C2F5SO2)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium aliphatic carboxylates having 4 or less carbon atoms, lithium tetraphenylborate, and lithium imide. However, in order to achieve the objectives of the present invention, it is preferable to contain only lithium bis(pentafluoroethanesulfonyl)imide as the lithium salt.

[0026] The concentration of the lithium salt may be determined in consideration of ion conductivity, etc., and may be 1 M to 1.8 M, preferably 1.2 M to 1.5 M. If the concentration of the lithium salt is less than 1 M, it may be difficult to ensure ion conductivity suitable for battery operation, and if it exceeds 1.8 M, the viscosity of the electrolyte may increase, reducing the mobility of lithium ions, or the decomposition reaction of the lithium salt itself may increase, reducing the performance of the battery.

[0027] In the electrolyte containing the first solvent, the second solvent and the lithium salt, the molar ratio of the lithium salt, the second solvent and the first solvent is 1:1.5-2.7:2.8-5, preferably 1:1.7-2.7:2.8-4.5, more preferably 1:1.9-2.4:3.1-3.6. If the molar ratio of the lithium salt, the second solvent and the first solvent is out of the above range (1:1.5-2.7:2.8-5), the discharge capacity and life performance of the battery are reduced, making it impossible to achieve the object of the present invention.

[0028] In addition, as can be seen from the range of the molar ratio of the lithium salt, the second solvent, and the first solvent, the present invention is characterized in that the first solvent containing a fluorine-based ether compound is contained in the electrolyte at a higher content ratio than the second solvent containing a glyme-based compound. In this way, when the first solvent containing a fluorine-based ether compound is contained at a higher content ratio than the second solvent containing a glyme-based compound, it is advantageous in that it suppresses the generation of polysulfides, thereby enabling the realization of a battery capacity close to the theoretical capacity of sulfur, and suppressing the decrease in battery capacity due to the use of the battery. Therefore, the first solvent containing a fluorine-based ether compound must be contained at a higher content ratio (molar ratio) than the second solvent containing a glyme-based compound.

[0029] D) positive electrode The lithium-sulfur battery according to the present invention includes a positive electrode including sulfur and a carbon material as active materials, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte including A) a first solvent including a fluorinated ether compound, B) a second solvent including a glyme compound, and C) a lithium salt as described above. The positive electrode will be described in detail below.

[0030] The positive electrode included in the lithium-sulfur battery of the present invention includes a positive electrode active material, a binder, and a conductive material. The positive electrode may be a base solid material including an active material, a binder, and a conductive material disposed on a current collector. The positive electrode active material may be any material applicable to conventional lithium-sulfur batteries, and may include, for example, elemental sulfur (S8), a sulfur-based compound, or a mixture thereof. Specifically, the sulfur-based compound is Li2S n (n ≥ 1), organic sulfur compounds or sulfur-carbon complexes ((C2S x ) n (x=2.5 to 50, n≧2) The positive electrode active material may include a sulfur-carbon composite, and since the sulfur material alone does not have electrical conductivity, it may be used in combination with a conductive material.

[0031] The sulfur-carbon composite may have a particle size of 1 to 100 μm. If the particle size of the sulfur-carbon composite is less than 1 μm, the resistance between particles increases, which may cause overvoltage in the electrode of the lithium-sulfur battery. If the particle size exceeds 100 μm, the surface area per unit weight is reduced, which reduces the wetting area with the electrolyte in the electrode and the reaction site with lithium ions, and the amount of electron transfer is reduced compared to the size of the composite, which slows down the reaction, which may reduce the discharge capacity of the battery.

[0032] The sulfur (S) may be included in an amount of 60 to 80 wt %, preferably 67.5 to 75 wt %, based on the total weight of the positive electrode. The sulfur content in the positive electrode of a conventional lithium-sulfur battery is about 40 to 60 wt % based on the total weight of the positive electrode, and the present invention uses sulfur at a significantly higher content than this, but shows a high initial discharge capacity under the electrolyte conditions of the present invention. If the sulfur is used in an amount less than 60 wt % based on the total weight of the positive electrode, a problem of a decrease in the energy density of the battery may occur, and if it is used in an amount exceeding 80 wt %, a problem of a decrease in the conductivity in the electrode and a decrease in the stability of the electrode may occur.

[0033] The carbon material (or sulfur carrier) constituting the sulfur-carbon composite has porosity. In particular, the carbon material used in the positive electrode active material of the present invention has a high specific surface area (1,700 m 2 / g or more, preferably 3,000m 2 / g or more) and high porosity (Pore Volume: 0.7~3cm 3 / g), the electrolyte allows for high-capacity (1,340 to 1,675 mAh / g) operation.

[0034] The porous carbon material is 0.7 to 3 cm 3 The carbonaceous materials having a pore volume of 0.7 to 3 cm / g can be exemplified. 3Graphite that fills a pore volume of 1000 nm / g; graphene; reduced graphene oxide (rGO); carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon nanotubes (CNT) such as single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT); carbon fibers such as graphite nanofibers (GNF), carbon nanofibers (CNF), and activated carbon fibers (ACF); and activated carbon; and the like may be shaped like a sphere, a rod, a needle, a plate, a tube, or a bulk.

[0035] The positive electrode active material containing sulfur and carbon material may be included in an amount of 80 to 99 parts by weight, preferably 90 to 95 parts by weight, based on 100 parts by weight of the total weight of the positive electrode. If the content of the positive electrode active material is less than 80 parts by weight based on 100 parts by weight of the total weight of the positive electrode, a problem of a decrease in the energy density of the battery may occur, and if it exceeds 99 parts by weight, a problem of a decrease in the conductivity in the electrode and a decrease in the stability of the electrode may occur. Meanwhile, the "total weight of the positive electrode" used to indicate the content of sulfur and the content of the positive electrode active material above means the remainder excluding the positive electrode current collector, i.e., the total content of the positive electrode active material, binder, and conductive material.

[0036] The binder is a component that aids in binding the positive electrode active material and the conductive material and the current collector, and may be, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polyvinylpyrrolidone, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butylene rubber, fluororubber, carboxymethylcellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, and mixtures thereof, but is not limited thereto.

[0037] The binder is typically added in an amount of 1 to 50 parts by weight, preferably 3 to 15 parts by weight, based on 100 parts by weight of the total weight of the positive electrode. If the content of the binder is less than 1 part by weight, the adhesive strength between the positive electrode active material and the current collector may be insufficient, and if the content of the binder exceeds 50 parts by weight, the adhesive strength is improved, but the content of the positive electrode active material is accordingly reduced, resulting in a lower battery capacity.

[0038] The conductive material contained in the positive electrode is not particularly limited as long as it has excellent electrical conductivity without causing side reactions in the internal environment of the battery and without causing chemical changes in the battery. Representative examples include graphite or conductive carbon. For example, graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, and lamp black; carbon-based materials having a graphene or graphite crystal structure; carbon nanotubes; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. These may be used alone or in combination, but are not necessarily limited thereto.

[0039] The conductive material may be added in an amount of 0.5 to 10 parts by weight, preferably 0.5 to 5 parts by weight, based on 100 parts by weight of the total weight of the positive electrode, but may not be included in the positive electrode of the present invention. If the content of the conductive material is too high, exceeding 10 parts by weight, the amount of the positive electrode active material may be relatively reduced, resulting in a decrease in capacity and energy density. There are no significant limitations on the method of including the conductive material in the positive electrode, and any conventional method known in the art, such as coating the positive electrode active material, may be used. In addition, if necessary, a conductive second coating layer may be added to the positive electrode active material instead of adding the conductive material.

[0040] In addition, a filler may be selectively added to the positive electrode of the present invention as a component for suppressing the expansion of the electrode. Such a filler is not particularly limited as long as it can suppress the expansion of the electrode without causing a chemical change in the battery, and examples of such fillers include olefin polymers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber; and the like.

[0041] The positive electrode may be manufactured by dispersing and mixing the positive electrode active material, binder, conductive material, etc. in a dispersion medium (solvent) to prepare a slurry, which is then coated on a positive electrode current collector, and then dried and rolled. The dispersion medium may be, but is not limited to, NMP (N-methyl-2-pyrrolidone), DMF (dimethyl formamide), DMSO (dimethyl sulfoxide), ethanol, isopropanol, water, or a mixture thereof.

[0042] The positive electrode current collector may be, but is not limited to, platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (In doped SnO2), FTO (F doped SnO2), and alloys thereof, and aluminum (Al) or stainless steel surface-treated with carbon (C), nickel (Ni), titanium (Ti), or silver (Ag). The positive electrode current collector may be in the form of a foil, a film, a sheet, a punched piece, a porous body, a foam, or the like.

[0043] The negative electrode is a lithium-based metal, and may further include a current collector on one side of the lithium-based metal. The current collector may be a negative electrode current collector. The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be selected from the group consisting of copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy, or may be a non-conductive polymer or a conductive polymer surface-treated with a conductive material. In general, a copper thin plate is used as the negative electrode current collector.

[0044] In addition, the negative electrode current collector may be in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with or without fine unevenness on the surface. In addition, the negative electrode current collector is applied to have a thickness of 3 to 50 μm. If the thickness of the negative electrode current collector is less than 3 μm, the current collecting effect is reduced, while if the thickness exceeds 50 μm, there is a problem that the workability is reduced when the cell is folded and assembled.

[0045] The lithium-based metal may be lithium or a lithium alloy. In this case, the lithium alloy may include an element capable of being alloyed with lithium, specifically, an alloy of lithium and at least one selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al. The lithium-based metal may be in the form of a sheet or foil, and may be in the form of lithium or a lithium alloy deposited or coated on a current collector by a dry process, or in the form of metal or alloy deposited or coated on particles by a wet process, etc.

[0046] A conventional separator may be interposed between the positive electrode and the negative electrode. The separator is a physical separator having a function of physically separating the electrodes, and may be any separator that is used in conventional separators without any particular limitations. In particular, the separator is preferably one that has low resistance to ion movement of the electrolyte and has excellent electrolyte moisture-retaining ability. In addition, the separator separates or insulates the positive electrode and the negative electrode from each other, allowing lithium ions to be transported between the positive electrode and the negative electrode. Such a separator may be made of a porous, non-conductive or insulating material. The separator may be an independent member such as a film, or a coating layer added to the positive electrode and / or the negative electrode.

[0047] Examples of polyolefin-based porous membranes that can be used for the separation membrane include membranes formed of polyolefin-based polymers such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene), polypropylene, polybutylene, polypentene, etc., either alone or in combination. Examples of nonwoven fabrics that can be used in the separator include nonwoven fabrics made of polymers such as polyphenyleneoxide, polyimide, polyamide, polycarbonate, polyethyleneterephthalate, polyethylenenaphthalate, polybutyleneterephthalate, polyphenylenesulfide, polyacetal, polyethersulfone, polyetheretherketone, and polyester, either alone or in combination. Such nonwoven fabrics include spunbond or meltblown fabrics made of long fibers as a fiber form forming a porous web.

[0048] The thickness of the separator is not particularly limited, but is preferably in the range of 1 to 100 μm, and more preferably in the range of 5 to 50 μm. If the thickness of the separator is less than 1 μm, it cannot maintain its mechanical properties, and if it exceeds 100 μm, the separator acts as a resistance layer, resulting in a decrease in battery performance. The pore size and porosity of the separator are not particularly limited, but it is preferable that the pore size is 0.1 to 50 μm and the porosity is 10 to 95%. If the pore size of the separator is less than 0.1 μm or the porosity is less than 10%, the separator acts as a resistance layer, and if the pore size is more than 50 μm or the porosity is more than 95%, the separator cannot maintain its mechanical properties.

[0049] The lithium-sulfur battery of the present invention including the above-mentioned electrolyte, positive electrode, negative electrode, and separator may be manufactured by a process of placing a positive electrode and a negative electrode facing each other, interposing a separator therebetween, and then injecting an electrolyte.

[0050] Meanwhile, the lithium-sulfur battery according to the present invention can be applied to a battery cell used as a power source for a small device, and can be particularly suitable for use as a unit battery of a battery module that is a power source for a medium-sized or large device. In this respect, the present invention also provides a battery module including two or more lithium-sulfur batteries electrically connected (series or parallel). The number of lithium-sulfur batteries included in the battery module can be adjusted in various ways in consideration of the use and capacity of the battery module. Furthermore, the present invention provides a battery pack in which the battery modules are electrically connected according to a conventional technique in the art. The battery module and the battery pack can be used as a power source for one or more medium-sized or large devices including, but not limited to, a power tool; an electric vehicle (EV), a hybrid electric vehicle (HEV), and an electric vehicle (PHEV), including a plug-in hybrid electric vehicle (PHEV); an electric truck; an electric commercial vehicle; or a power storage system.

[0051] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention, and it is natural that such changes and modifications fall within the scope of the accompanying claims.

[0052] [Example 1] Lithium-sulfur battery manufacturing electrolyte manufacturing First, lithium bis(pentafluoroethanesulfonyl)imide (LiBETI, concentration: 1.2 M), dimethoxyethane (DME, second solvent), and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE, first solvent) were mixed in a molar ratio of 1:2.4:3.6 at room temperature to prepare an electrolyte for lithium-sulfur batteries.

[0053] Cathode Manufacturing The positive electrode active material was a sulfur-carbon composite (S:C = 75:25 weight ratio) of 90 parts by weight (the content of sulfur alone was set to 67.5% by weight based on the total weight of the positive electrode, and the carbon material had a pore volume of 1.8 cm 3 A positive electrode slurry composition was prepared by mixing 5 parts by weight of activated carbon having a capacity of 1.5 mAh / g, 5 parts by weight of denka black as a conductive material, and 5 parts by weight of styrene butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3) as a binder. The slurry composition was then coated on a current collector (Aluminum foil), dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode (the loading amount was 3.5 mAh / cm). 2 The porosity of the electrode was set to 65%.

[0054] Lithium-sulfur battery manufacturing The prepared positive electrode and a lithium metal negative electrode having a thickness of 150 μm were placed facing each other, a polyethylene (PE) separator was interposed between them, and the prepared electrolyte was injected to prepare a coin cell type lithium-sulfur battery. Meanwhile, in manufacturing the battery, the positive electrode was punched out to be a circular electrode of 14 phi, the polyethylene separator was punched out to be 19 phi, and the lithium metal was punched out to be 16 phi.

[0055] [Example 2, Comparative Examples 1 to 4] Lithium-sulfur battery manufacturing Lithium-sulfur batteries corresponding to Example 2 and Comparative Examples 1 to 4 were manufactured in the same manner as in Example 1, except that the electrolyte composition of the lithium-sulfur battery of Example 1 was changed as shown in Table 1 below.

[0056] [Table 1]

[0057] [Experimental Example 1] Discharge capacity and life characterization of lithium-sulfur batteries. The lithium-sulfur batteries prepared in Example 1, Example 2, and Comparative Examples 1 to 4 were charged and discharged for 50 cycles at 0.5 C to evaluate the discharge capacity and life characteristics of the batteries. The voltage range used was 1.5 to 3.0 V (i.e., discharge up to 1.5 V, charge up to 3.0 V), and the evaluation was performed at room temperature.

[0058] 1 is a graph showing the discharge capacity and life characteristics of the lithium-sulfur battery manufactured according to an embodiment of the present invention and a comparative example. It has been explained that in the electrolyte contained in the lithium-sulfur battery of the present invention, the molar ratio of the lithium salt, the second solvent, and the first solvent is 1:1.5-2.7:2.8-5, preferably 1:1.7-2.7:2.8-4.5, and more preferably 1:1.9-2.4:3.1-3.6.

[0059] In addition, it was confirmed that the lithium-sulfur batteries of Examples 1 and 2, in which the mixed molar ratios of the lithium salt, second solvent, and first solvent contained in the electrolyte are within the range of 1:1.5-2.7:2.8-5, respectively, have much better initial discharge capacity and life characteristics than the lithium-sulfur batteries of Comparative Examples 1 to 3, in which the mixed molar ratios of the lithium salt, second solvent, and first solvent contained in the electrolyte are not within the range of 1:1.5-2.7:2.8-5, as shown in Figure 1. In other words, even if the types of lithium salt and solvent are the same, it is impossible to improve battery performance unless they are mixed in a specific ratio.

[0060] Meanwhile, in the lithium-sulfur battery of Comparative Example 4, even though the molar ratio of the lithium salt, second solvent, and first solvent contained in the electrolyte was the same as that of Example 2, the discharge capacity rapidly decreased and the life performance also decreased compared to Example 2 after about 25 cycles as shown in Figure 1. This is due to the difference in the type of lithium salt as can be seen from Table 1, and it can be seen that the discharge capacity and life characteristics of the battery are improved by using LiBETI as the lithium salt instead of the commonly used LiTFSI.

Claims

1. An electrolyte comprising a first solvent containing a fluorinated ether compound, a second solvent containing a glyme compound, and a lithium salt containing lithium bis(pentafluoroethanesulfonyl)imide; and a positive electrode including sulfur and a carbon material as active materials; The molar ratio of the lithium salt, the glyme-based compound, and the fluorine-based ether compound contained in the electrolyte is 1:1.5-2.7:2.8-5; The fluorine-based ether compound includes at least one selected from the group consisting of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), bis(fluoromethyl)ether, 2-fluoroethyl methyl ether, bis(2,2,2-trifluoroethyl)ether, propyl 1,1,2,2-tetrafluoroethyl ether, isopropyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl isobutyl ether, 1,1,2,3,3,3-hexafluoropropyl ethyl ether, 1H,1H,2′H,3H-decafluorodipropyl ether, and 1H,1H,2′H-perfluorodipropyl ether; The glyme-based compound includes at least one selected from the group consisting of dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.

2. 2. The lithium-sulfur battery of claim 1, wherein the concentration of the lithium salt is 1M to 1.8M.

3. 2. The lithium-sulfur battery of claim 1, wherein the electrolyte is free of nitrile-based solvents.

4. 2. The lithium-sulfur battery of claim 1, wherein the sulfur is contained in an amount of 60% to 80% by weight based on the total weight of the positive electrode.

5. The pore volume of the carbon material is 0.7 cm 3 / g to 3 cm 3 / g, and the specific surface area is 1,700 m 2 2. The lithium-sulfur battery of claim 1, wherein the Sr content is 1.0 / g or more.

6. 2. The lithium-sulfur battery of claim 1, wherein the positive electrode active material comprises a sulfur-carbon composite.

7. 2. The lithium-sulfur battery according to claim 1, wherein the utilization rate of the sulfur contained in the positive electrode is 80% or more of the theoretical discharge capacity.

8. 2. The lithium-sulfur battery of claim 1, wherein the energy density of the lithium-sulfur battery is 400 Wh / kg or more or 600 Wh / L or more.

9. 2. The lithium-sulfur battery of claim 1, wherein the first solvent is 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), the second solvent is dimethoxyethane (DME), and the lithium salt is lithium bis(pentafluoroethanesulfonyl)imide (LiBETI).

10. 10. The lithium-sulfur battery according to claim 1, wherein the molar ratio of the lithium salt, the glyme-based compound and the fluorine-based ether compound is 1:1.9-2.4:3.1-3.6.

Citation Information

Patent Citations

  • Electrolyte for lithium-sulfur battery, and lithium-sulfur battery including the electrolyte for lithium-sulfur battery

    JP2005108438A

  • Nonaqueous electrolyte and nonaqueous electrolyte power storage element

    JP2019046759A

  • Electrolyte for lithium-sulfur battery and lithium-sulfur battery comprising the same

    KR1020210127329A